Renal Contrast‐Enhanced Sonography Findings in a Model of Acute Cellular Allograft Rejection. Issue 5 (26th February 2016) - Grabner, A.; Kentrup, D.; Pawelski, H.; Mühlmeister, M.; Biermann, C.; Edemir, B.; Heitplatz, B.; Van Marck, V.; Bettinger, T.; Pavenstädt, H.; Schlatter, E.; Stypmann, J.; et al.
Abstract : Noninvasive methods to diagnose and differentiate acute cellular rejection from acute tubular necrosis or acute calcineurin inhibitor toxicity are still missing. Because T lymphocytes play a decisive role in early states of rejection, we investigated the suitability and feasibility of antibody‐mediated contrast‐enhanced ultrasound by using microbubbles targeted to CD3 +, CD4 +, or CD8 + T cells in different models of renal disease. In an established rat renal transplantation model, CD3‐mediated ultrasound allows the detection of acute rejection as early as on postoperative day 2. Ultrasound signal intensities increased with the severity of inflammation. Further, an early response to therapy could be monitored by using contrast‐enhanced sonography. Notably, acute tubular necrosis occurring after ischemia–reperfusion injury as well as acute calcineurin inhibitor toxicity could easily be differentiated. Finally, the quantified ultrasound signal correlated significantly with the number of infiltrating T cells obtained by histology and with CD3 mRNA levels, as well as with chemokine CXCL9, CXCL11, and CCL19 mRNA but not with KIM‐1 mRNA expression, thereby representing the severity of graft inflammation but not the degree of kidney injury. In summary, we demonstrate that antibody‐mediated contrast‐enhanced ultrasound targeting T lymphocytes could be a promising tool for an easy and reproducible assessment of acute rejection after renal transplantation. Abstract : Renal contrast‐enhanced sonography targeting CD3 assists in the differential diagnosis of acute allograft injury in an animal model of kidney transplantation.